Multiple literary identities in contemporary Malaysian literature: an analysis of readers’ views on Heroes by Karim Raslan - Jerome, Collin; Ruzy Suliza Hashim,; Ting, Su-Hie (Penerbit Universiti Kebangsaan Malaysia, 2016)
Contemporary Malaysian literature not only provides an avenue for creative expression, but also functions as a site for identity creation where writers create multiple identities for their characters. While many studies have examined specific identities possessed by the characters, there is still a need for more research on the multiplicity of literary identities and how they affect readers’ understanding of the characters’ identities and their own identities in the process. This paper presents readers’ views on the construction of multiple literary identities in Karim Raslan’s Heroes. Drawing on the tenets of sociocultural and literary theories, the paper examines readers’ (1) views on the author’s construction and portrayal of the characters’ identities, and (2) understanding of these identities and their own identities in the process. The readers were two undergraduate students from a public university in Malaysia who volunteered to read and respond critically to the author’s work, and share their views about the characters’ identities. The analysis revealed that the author used a wide range of words and phrases to construct the characters’ identities based on ethnicity, religion, gender, familial roles, social rank, place, and profession. While acknowledging that some of these identities overlapped with each other as part and parcel of being Malaysian, the readers opined that the characters’ physical features, feelings and emotions, and values associated to identities could be included into the authorial construction of characters’ identities. Furthermore, while the readers claimed that the author’s identity portrayal enhanced their understanding of the characters’ identities and their own identities in the process, they sought an avenue to challenge such portrayal, given that they too create multiple identities in the narrative of their lives.